Interface Jacobian‐based Co‐Simulation. (3rd March 2014) - Sicklinger, S.; Belsky, V.; Engelmann, B.; Elmqvist, H.; Olsson, H.; Wüchner, R.; Bletzinger, K.‐U.
SUMMARY Co‐simulation is a prominent method to solve multi‐physics problems. Multi‐physics simulations using a co‐simulation approach have an intrinsic advantage. They allow well‐established and specialized simulation tools for different fields and signals to be combined and reused with minor adaptations in contrast to the monolithic approach. However, the partitioned treatment of the coupled system poses the drawback of stability and accuracy challenges. If several different subsystems are used to form the co‐simulation scenario, these issues are especially important. In this work, we propose a new co‐simulation algorithm based on interface Jacobians. It allows for the stable and accurate solution of complex co‐simulation scenarios involving several different subsystems. Furthermore, the Interface Jacobian‐based Co‐Simulation Algorithm is formulated such that it enables parallel execution of the participating subsystems. This results in a high‐efficient procedure. Furthermore, the Interface Jacobian‐based Co‐Simulation Algorithm handles algebraic loops as the co‐simulation scenario is defined in residual form. Copyright © 2014 John Wiley & Sons, Ltd.